Preparing Financial Reports Using Microsoft Excel Based on SAK EMKM (Case Study of Various Kiosk Umkm) in Manado - Tuerah, Raykes Hinrich; Maradesa, Christony; Kesek, Meike Negawati; Ruhiyat, Ruhiyat (CV. Rayyan Dwi Bharata, 2024)
Kios Aneka's business has only been running for 2 years now. Kios Aneka has 2 types of business, namely the gas trading business and the advertising agency business. According to an interview with the kiosk owner, currently the business is running well but not too significantly, he added that currently additional business capital is needed by borrowing capital from banks or other sources. However, the current obstacle is regarding information in submitting financial report documents for administration to the bank or other partners in lending capital. The type of research used in this research is qualitative research. Based on the results of processed financial reports based on SAK EMKM using Microsoft Excel, this report summarizes all income and expenses for one period, including the cumulative impact of income, profits, expenses and losses on Kios Aneka MSMEs. The balance sheet is an accounting report that summarize Kios Aneka's assets (current, long-term and intangible assets). On the liabilities side, there are liabilities (debts, bills and bank loans) and equity (share capital and profits). Notes to financial statements (CALK) are notes or additional information added to the end of a financial report. Based on the results of research conducted at Kios Aneka, it can be concluded that the owner of Kios Aneka does not prepare financial reports based on accounting standards for micro, small and medium enterprises (SAK EMKM), because entrepreneurs do not have knowledge of accounting and accounting standards for micro, small and medium enterprises (SAK EMKM).